2020
DOI: 10.1007/s40544-020-0445-5
|View full text |Cite
|
Sign up to set email alerts
|

Structure and tribocorrosion behavior of CrMoSiCN nanocomposite coating with low C content in artificial seawater

Abstract: CrMoSiCN nanocomposite coatings with a low C content were prepared on Ti-6Al-4V using an unbalanced magnetron sputtering system, and their corresponding microstructures, mechanical properties, and tribocorrosion performance were evaluated in detail. The results revealed that the CrMoSiCN coating had a compact nanocomposite microstructure consisting of CrN and Mo2N nanocrystallites, (Cr, Mo)N solid solution, and Si-C-N amorphous phases. Moreover, the coating exhibited superior mechanical properties with a hardn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(1 citation statement)
references
References 50 publications
0
0
0
Order By: Relevance
“…The author discovered that these coatings exhibited varying tribocorrosion behaviors, which were influenced by the Ag target current. The study revealed that with an increase in the Ag current, the tribocorrosion mechanisms of CrMoSiCN/Ag coatings shifted, highlighting different wear resistance levels under varying conditions [226][227][228][229]. Different PVD coatings like TiAlCN and TiSiN/Ag were studied by Li, including nitrided TiSiCN.…”
Section: Marine and Offshore Sectormentioning
confidence: 99%
“…The author discovered that these coatings exhibited varying tribocorrosion behaviors, which were influenced by the Ag target current. The study revealed that with an increase in the Ag current, the tribocorrosion mechanisms of CrMoSiCN/Ag coatings shifted, highlighting different wear resistance levels under varying conditions [226][227][228][229]. Different PVD coatings like TiAlCN and TiSiN/Ag were studied by Li, including nitrided TiSiCN.…”
Section: Marine and Offshore Sectormentioning
confidence: 99%